2012
DOI: 10.1111/j.1423-0410.2011.01581.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐yield Platelet units revealed immediate pH decline and delayed mitochondrial dysfunction during storage in 100% plasma as compared with storage in SSP+

Abstract: The use of SSP+ instead of plasma may reduce the risk of triggering pro-apoptotic events in high-yield PLT units. A rapid decline in pH in PLT units cannot be explained with initial elevated and prolonged high carbon dioxide levels and mitochondrial dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…33 Also the expression level of the GPIb-IX-V complex 34,35 and maintenance of the PECAM-1 (CD31) levels of filtered PLTs 36,37 strengthens the conclusion that filtration does not adversely affect PLT quality. Moreover, our results on the filtered PLTs seem to agree with the functional integrity of the OrbiSac-produced PLTs proven earlier in a series of in vitro assays 2,22,23,29,30,37 and more than 10 years of clinical experience including more than 1.5 million units produced worldwide.…”
Section: Effect Of Storage Postrecovery Filtration and Activated Masupporting
confidence: 90%
See 1 more Smart Citation
“…33 Also the expression level of the GPIb-IX-V complex 34,35 and maintenance of the PECAM-1 (CD31) levels of filtered PLTs 36,37 strengthens the conclusion that filtration does not adversely affect PLT quality. Moreover, our results on the filtered PLTs seem to agree with the functional integrity of the OrbiSac-produced PLTs proven earlier in a series of in vitro assays 2,22,23,29,30,37 and more than 10 years of clinical experience including more than 1.5 million units produced worldwide.…”
Section: Effect Of Storage Postrecovery Filtration and Activated Masupporting
confidence: 90%
“…All methods, including staining, were performed as described in recent publications. 23,29,30 Secretion markers and cytokine analysis …”
Section: Analysis Of Cellular Metabolic In Vitro Functional and Phementioning
confidence: 99%
“…Measurements of extracellular parameters offer, on one hand, valuable insights into the equilibrium among the cytosolic pathways and the mitochondrial oxidative pathways of PLTs during storage, as changes caused by PLTs may disturb metabolic homeostasis are linked to increased cytosolic glycolysis , PLT activation , aggregation and release reactions . On the other hand, other physiological challenges, not related to increased glycolytic flux and accelerated cellular metabolism, may affect metabolic homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…This proton gradient uncoupling agent quickly reduces the electrochemical potential across the inner mitochondrial membrane, resulting in a rapid intracellular mitochondrial depolarization event. Maintenance of MMP is expressed as JC‐1‐positive PLTs as described earlier .…”
Section: Methodsmentioning
confidence: 99%
“…They are one of the life-saving transfusion products in controlling bleeding associated with surgery, trauma, and accident victims in day-to-day life. During storage under standard blood bank conditions, platelets normally start to lose their quality with time and it has been identified that one of the reasons for this loss of quality is due to mitochondrial dysfunction [13]. Understanding the molecular mechanisms underlying mitochondrial dysfunction and ATP regulation in platelets during storage would facilitate developing targeted strategies toward enhancing the shelf-life of ex vivo stored platelets.…”
Section: Introductionmentioning
confidence: 99%